MULLA HADI SABZAWARI AS A LEADING LATER SADRIAN PHILOSOPHER: REVISITING HIS LIFE AND WORKS - Rizky Febrian (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The purpose of this article is to revisit the life and significant works of the nineteenth-century Persian philosopher Mulla Hadi Sabzawari (d. 1873). He was the foremost exponent of theosophical traditions who studied and elaborated the metaphysical discourse in great detail. He was also renowned for his commentary on Mulla Sadra’s (d. 1640) al-Asfar and al-Shawahid al-Rububiyyah, as well as for reviving Sadra’s teachings. The best example of Sabzawari’s philosophical theory, which he developed and expounded, is recorded in his magnum opus, the commentary of Ghurar al-Fara’id. His ideas and writings influenced many Persian intellectuals who came after him. This article also re-examines some conclusions by previous reseachers regarding the study on Sabzawari. This will be followed by a brief explanation on the characteristics of Sabzawari’s works, including its style and structure of writing, the content of the discussion, and its significance. This study is based on a qualitative method to arrive at conclusions in which content analysis is utilized in describing the life and works of Sabzawari.